2019 28th International Conference on Computer Communication and Networks (ICCCN) 2019
DOI: 10.1109/icccn.2019.8847051
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Socioeconomic Status via Temporal-Spatial Mobility Analysis - A Case Study of Smart Card Data

Abstract: The notion of socioeconomic status (SES) of a person or family reflects the corresponding entity's social and economic rank in society. Such information may help applications like bank loaning decisions and provide measurable inputs for related studies like social stratification, social welfare and business planning. Traditionally, estimating SES for a large population is performed by national statistical institutes through a large number of household interviews, which is highly expensive and time-consuming. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 33 publications
(58 reference statements)
0
10
0
Order By: Relevance
“…To reduce the manpower needed for fine-grained income surveys and to speed up fine-grained income data collection, researchers have used house price as a proxy for income. Previous studies have identified a positive correlation between house price and income [23][24][25][26][27][28][29], whilst house price data are easily accessible and downloadable online in the developed world. However, estimation models that depend on house price as the input and income as the output have yielded a low estimation accuracy.…”
mentioning
confidence: 99%
“…To reduce the manpower needed for fine-grained income surveys and to speed up fine-grained income data collection, researchers have used house price as a proxy for income. Previous studies have identified a positive correlation between house price and income [23][24][25][26][27][28][29], whilst house price data are easily accessible and downloadable online in the developed world. However, estimation models that depend on house price as the input and income as the output have yielded a low estimation accuracy.…”
mentioning
confidence: 99%
“…Lately, Zhang and Cheng (2018) explored inferring demographics by leveraging a variety of spatial and temporal features extracted from the raw transaction records. Ding, Huang, Zhao and Fu (2019) developed a deep learning model to estimate socioeconomic status using temporal-sequential features and general statistical features generated from SC data. However, the success of these works heavily relied on elaborated feature engineering.…”
Section: Demographic Inference Using Geo-tagged Datamentioning
confidence: 99%
“…Another important user-generated data type is mobile phone data. However, most of the existing studies only focus on group-level SES inference (at least until the acceptance of our work [25] in 2019). Soto et al explore how to use information derived from the aggregated use of cell phone records to identify the socioeconomic levels of a population [87].…”
Section: Ses Estimation Based On Cell Phone Datamentioning
confidence: 99%
“…And in the end, researchers utilize a commonly-used machine learning algorithm, the ridge regression model, to predict the logged income of Facebook users. tweets SES [73] tweets income [58] tweets income [93] tweets education, income [4] tweets occupation, income [40] tweets income [94] tweets education, income [95] tweets education, income [14] tweets family income [61] Facebook Likes income [13] mobile phone metadata personal income [87] mobile phone records SES [29] mobile phone call detail records income [12] mobile phone metadata income [90] mobile phone metadata income [8] cookie income, education level [68] retail transaction records income,education level [96] retail transaction records income, education level [25] smart card transportation records SES [74] WiFi log education, income…”
Section: Sea Inference Based On Social Media Datamentioning
confidence: 99%
See 1 more Smart Citation